Identification of compound D2923 as a novel anti-tumor agent targeting CSF1R. (November 2018) - Liu, Ying-Qiang; Wang, Ya-Nan; Lu, Xiao-Yun; Tong, Lin-Jiang; Li, Yan; Zhang, Tao; Xun, Qiu-Ju; Feng, Fang; Chen, Yu-Zhe; Su, Yi; Shen, Yan-Yan; Chen, Yi; et al.
Abstract Colony-stimulating factor 1 receptor (CSF1R) plays a critical role in promoting tumor progression in various types of tumors. Here, we identified D2923 as a novel and selective inhibitor of CSF1R and explored its antitumor activity both in vitro and in vivo. D2923 potently inhibited CSF1R in vitro kinase activity with an IC50 value of 0.3 nM. It exhibited 10- to 300-fold less potency against a panel of kinases tested. D2923 markedly blocked CSF-1-induced activation of CSF1R and its downstream signaling transduction in THP-1 and RAW264.7 macrophages and thus inhibited the in vitro growth of macrophages. Moreover, D2923 dose-dependently attenuated the proliferation of a small panel of myeloid leukemia cells, mainly by arresting the cells at G1 phase as well as inducing apoptosis in the cells. The results of the in vivo experiments further demonstrated that D2923 displayed potent antitumor activity against M-NFS-60 xenografts, with tumor growth inhibition rates of 50% and 88% at doses of 40 and 80 mg/kg, respectively. Additionally, D2923 was well tolerated with no significant body-weight loss observed in the treatment groups compared with the control. Furthermore, a western blot analysis and the immunohistochemistry results confirmed that the phosphorylation of CSF1R in tumor tissue was dramatically reduced after D2923 treatment, and this was accompanied by the depletion of macrophages in the tumor. Meanwhile, the expression of the proliferation marker Ki67 was also markedly decreased in the D2923 treatment group compared with the control group. Taken together, we identified D2923 as a novel and effective CSF1R inhibitor, which deserves further investigation.